DULOXETINE HYDROCHLORIDE INDUCED PARESTHESIA - A CASE REPORT - AR, SAI PAWAN; Srivastava, Birendra; Adepu, Ramesh (Asian Journal of Pharmaceutical and Clinical Research, 2023)
A 45-year-old HIV-positive female patient experienced a generalized burning sensation after the administration of one dose of duloxetine 20 mg. The patient’s concurrent medications include a fixed drug combination of nevirapine 200 mg, Lamivudine 150 mg, and Zidovudine 300 mg, twice daily for 5 years. The patient recovered from the generalized burning sensation the next day after the withdrawal of duloxetine. From the causal relationship assessment, we observed that neither the disease, comorbid conditions, nor concurrent medications were found responsible for the burning sensation experience in this patient. Available data from post-marketing surveillance of duloxetine suggest that to date the incidence of duloxetine-induced burning sensation of skin was reported to be 1 in 870 patients. Health-care providers should watch for this rare but important adverse effect of duloxetine.